Shared parenting and father involvement after divorce in Denmark - Sandberg, Kristian (Frontiers in Psychology, 2023)
The Scandinavian countries make interesting samples for the study of shared parenting as they are characterized by some of the highest levels of father involvement and gender equality globally. Despite numerous studies, data from Denmark is noticeably absent in the international debate, partly due to a researcher preference for publishing in Danish. Here, I present an overview of the increase in father involvement in Denmark since the 1960s and on the increase in shared parenting across recent decades. I further examine Danish law, ministerial guidelines and guidelines from major Danish public and private institutions/organizations involved in deciding or advising on parenting practices post-divorce. I relate these to international research findings as well as to findings from Danish research. Overall, I find that Danish guidelines/practice have several reservations against shared parenting and substantial father involvement, which are not considered warranted by a substantial number of scientists and which are not supported by the majority of the available evidence. It thus appears that societal transition towards increased shared parenting has happened on a largely voluntary basis in spite of official law/practice. Updated law and/or ministerial guidelines are likely necessary if politicians desire that children experience the same high degree of father involvement post-divorce that they experience in society in general.